Multi-functionalized fluorinated graphene composite coating for achieving durable electronics: Ultralow corrosion rate and high electrical insulating passivation. (15th August 2022) - Arshad, Muhammad Usama; Dutta, Dipak; Sin, Yu Yu; Hsiao, Shen Wu; Wu, Chih Yi; Chang, Bor Kae; Dai, Liming; Su, Ching Yuan
Abstract: Graphene is regarded as the best anticorrosion material; however, due to its inherent electrical conductivity, it, instead, greatly promotes galvanic corrosion when added as a filler above a certain loading threshold in a polymer composite coating. Electrically insulating 2D materials such as hexagonal boron nitride ( h -BN), which could be alternatives, also fail due to their poor dispersibility/compatibility with the polymer matrix, thus limiting their practical applications. Herein, we report a unique fluorinated graphene (FG), with optimizable F/C and C/O ratios (versatile surface chemistry properties), produced by scalable fluorination of facile and eco-friendly electrochemically exfoliated graphene (ECG, surface properties of which are tunable by varying electrochemical conditions) and propose a one-step and cost-effective fluorination route towards highly polymer matrix compatible composite for electronic passivation; in fact this alloys two steps optimization of surface functionalities leading to required properties of FG and the composite. By tuning and understanding their hydrophobicity, electrical conductivity, extent of fluorination, etc., through molecular dynamics (MD) simulations as well, with just 1% filler loading, the FG-polymer-composite shows the superior anticorrosion performance (corrosion rate (CR) = 7.83 × 10 −8  mm/year; current = 3.37 × 10 −12  A cm −2 ). Construction of a robust diffusion barrier indicated by a monotonic decrease in CR with FG loading leads FG to outperform other reported functionalized graphene and BN-related 2D materials. Extension of the use of FG composites to a nonmetallic substrate such as a flexible printed circuit board (PCB) is an original idea, and superior corrosion inhibition is achieved while preventing the risk of electrical short circuits due to the electrical insulating nature and the high breakdown voltage of FG; thus, making it a durable passivation layer on electronic devices, even in harsh environments. This work represents a breakthrough in anticorrosion technology and provides a novel strategy for exploring extremely impermeable composites for the long-term passivation of multi-functionalized electronics. Graphical abstract: The fluorinated graphene nanocomposite coating exhibit an ultralow corrosion rate and high electrical insulating, which is beneficial for archiving durable electronic passivation. Image 1